2001
DOI: 10.1053/eupc.2001.0185
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the left ventricle through the coronary sinus with a newly developed ‘over the wire’ lead system — early experiences with lead handling and positioning

Abstract: The new 'over the wire' lead and guiding catheter system allows uncomplicated access to the coronary sinus and the depth of the coronary vein tributaries. Left ventricular sensing and pacing thresholds are acceptable for chronic use in implanted cardiac rhythm management systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
2
11
0
1
Order By: Relevance
“…The LV stimulation threshold was unrelated to whether the LV pacing site was anterior or posterior/posteolateral acutely during follow‐up. Other studies support our findings with the highest LV stimulation thresholds in the basal or mid‐ventricular region of the lateral/posteolateral area of the LV 2,3 . In contrast, a study by Walker et al with 49 patients showed the lowest stimulation values in the basal region 4 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The LV stimulation threshold was unrelated to whether the LV pacing site was anterior or posterior/posteolateral acutely during follow‐up. Other studies support our findings with the highest LV stimulation thresholds in the basal or mid‐ventricular region of the lateral/posteolateral area of the LV 2,3 . In contrast, a study by Walker et al with 49 patients showed the lowest stimulation values in the basal region 4 .…”
Section: Discussionsupporting
confidence: 90%
“…R wave amplitude showed the best value at apical positions and this is supported by a prior study reported by Sack et al (NS) 2 . In contrast to Sack et al, we found significant better values for R wave amplitude in lateral/posteolateral positions (Group B) compared to anterior positions (Group A).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Los implantes realizados en pacientes con cardiopatía isquémica fueron más prolongados y tuvieron umbrales de estimulación ventricular izquierda mayores, reflejando una mayor dificultad técnica probablemente provocada por la existencia de áreas de miocardio necrosado e inexcitable. Desde nuestro punto de vista, en estos casos los sistemas de electrodo coaxial con guía de 0,014" son extremadamente útiles al permitir cartografiar múltiples zonas de miocardio y facilitar el desplazamiento por el sistema venoso cardíaco con relativa facilidad 20,21 . En nuestro estudio, el relativamente escaso número de pacientes y la subjetividad de algunas de las variables clínicas analizadas (clase funcional, número de ingresos), así como el propio diseño del trabajo, no permiten concluir inequívocamente que el beneficio clínico observado sea debido a la terapia.…”
Section: Discussionunclassified
“…According to several studies, the procedure is usually time consuming with long fluoroscopy times and the implantation success rate is reduced compared to conventional procedures (estimated between 90% to 97%) [52][53][54][55][56]. With the introduction of special delivery sheaths and the so-called 'over the wire technology' the breakthrough of LV pacing became reality in the early 2000s, yet lead stability remains problematic mainly due to different coronary sinus anatomies [57][58]. Because no muscular trabeculae is found in the CS for anchoring of the lead, the tip has to be pushed as distal as possible in a wedge position in a lateral or a postero-lateral CS branch and is typically non-actively fixated.…”
Section: Removal Of Left Ventricular Pacing Leadsmentioning
confidence: 99%